Attachable Iron Clothes / Muhammad Irsyad Sodiq Md Yamin - Md Yamin, Muhammad Irsyad Sodiq (2020)
Attachable Iron Clothes has many benefits compared to others normal iron clothes because we develop some new features which is very efficient on ironing the clothes and laundry on top of we enhance the safety of the products that why we develop this product. Our product has great quality and technology that can give satisfaction to the consumers. We applied some features which could cool down the sole plate of iron so can reduce the injury. Therefore, with our product, it could minimize the time taken to clothes because of the great features. Furthermore, we provide the affordable price with high quality material and long-lasting product so the consumers can use with long time. We develop this product in order to overcome the problem from previous issue that happen towards parents that have problem with burn effect because of the previous product. By this product development, they do not have to worry about the upcoming problem because we present a great function that will give more benefit to the consumers. Other than that, we implement with interesting design that will attract people to buy our product and easy to use.